Evaluating the attitudes of different trainee groups towards eye tracking enhanced safety training methods. (August 2021) - Comu, Semra; Kazar, Gokhan; Marwa, Zaki
Abstract: The primary approach to prevent injuries and fatalities on construction sites is to provide effective safety training to all site personnel. In order to develop an effective safety training method, it is critical to consider the attitudes of participants towards the training received. In this regard, the eye movements of three groups of trainees during both a conventional safety training method and a Virtual Reality (VR)-based training method were monitored. The eye-tracking data from five engineers, five workers, and five engineering students were collected to measure their time to first fixation and fixation durations of the three groups of AOIs (Areas of Interests). Accordingly, we identified their reaction to the training stimulus and measured their concentration and adaptation level. The data were analyzed using Mixed ANOVA with the between-subject variable of three different trainee groups and the within-subject variable of training types. The statistical findings showed that the engineers concentrate faster than the workers and the students during all sessions of safety training, and all participants spend more time exploring different AOIs during VR-based safety training. Therefore, it is concluded that the different backgrounds of study groups (e.g., field experience, site role, game experience, and education) play a crucial role in the adaptation and concentration level of the trainees during safety training sessions.